Feminist Collections, v.31, no.1-2 (winter-spring 2010) - (:unkn) unknown (My University, 2010)
Subtitle: A Quarterly of Women's Studies Resources. ISSN 0742-7441, 54p.
CONTENTS: From the Editors. Book & Film Reviews: Gender and Political Violence, by Janice Bogstad; The Mystique of the Female Sleuth, or, How I Stopped Worrying and Learned to Love a Good Clue, by Patricia Gott; Women and Literacy, by Martha Kaplan; Women in Prison, by Frances M. Kavenik. The Maine Women Writers Collection at the University of New England, by Jennifer S. Tuttle & Cally Gurley. Women's Compositions Online: Five Digital Collections, by Susan Wood. E-Sources on Women and Gender. New Reference Works in Women's Studies: Addiction, Colonial America, Folklore, Gender Roles, Girls, Health, Historical Queerness, Latin American Writers, LGBT Research, Literature, National History Day, Southern Gender, Women of Color, Women's Rights. Caveat Emptor. Periodical Notes Books and Videos Received.
Keywords: Incarcerated Women; Women Prisoners; Torture; Political Violence; Female Detectives; Digital Collections; Maine Women Writers Collection; Literacy; Terrorism; Women's Studies; Gender; Feminism; Library Resources; Reviews